2022
DOI: 10.1088/1757-899x/1220/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of a hybrid turbocharger main parameters applied to an internal combustion engine

Abstract: Internal combustion engines are constantly developing. Currently, a solution in full development is a hybrid car that has an internal combustion engine propulsion combined with an electrical motor. The electrical motor is powered by a battery which in turn is connected to other electricity suppliers for recharging. Therefore, the aim is to recover the thermal energy from the car, through various solutions, in order to transform it into electricity. Electricity is for the car’s battery as well as for its consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This is because an electric turbocharger can compensate for the reduced airflow caused by downsized engines, ensuring that the engine operates at optimal conditions. A few studies [22,26] found that a HET system improved the fuel efficiency and reduced emissions of a downsized engine by up to 15%.…”
Section: Electric Drive Of the Turbochargermentioning
confidence: 99%
“…This is because an electric turbocharger can compensate for the reduced airflow caused by downsized engines, ensuring that the engine operates at optimal conditions. A few studies [22,26] found that a HET system improved the fuel efficiency and reduced emissions of a downsized engine by up to 15%.…”
Section: Electric Drive Of the Turbochargermentioning
confidence: 99%